Islamic Femininity and Hijab Fashion: Negotiating Identity between Religiosity and Modernity in Indonesia - Rifqi, Pramidazzura Alifa (Kamara Journal, 2025)
This study examines how Indonesian Muslim women negotiate Islamic femininity through hijab fashion at the intersections of religiosity, modernity and digital visibility. Using a qualitative design grounded in Multimodal Critical Discourse Analysis, the research analyzes visual and textual materials from social media, hijab campaigns and online communities to uncover how hijab practices articulate evolving gendered identities. The findings show that hijab fashion functions as a cultural arena where women blend piety with contemporary aesthetic preferences, producing hybrid identities that challenge traditional boundaries of modesty. Digital platforms intensify this negotiation by enabling curated self presentation and exposing women to moral scrutiny, social expectations and aspirational beauty standards. Hijab influencers play a key role as cultural intermediaries who disseminate fashionable forms of piety shaped by consumer culture and global modest fashion trends. The study also reveals that women actively reinterpret religious obligations within liquid modernity, resisting singular definitions of Islamic femininity while navigating pressures from religious institutions, peer networks and online audiences. Overall, hijab fashion emerges as a dynamic site where Islamic identity, cultural creativity and modern aspirations converge. The study recommends future research on generational differences, algorithmic amplification of modest fashion and the global cultural circulation of Indonesian hijab aesthetics